RESISTENSI PARAMAECIUM CAUDATUM TERHADAP LOGAM TEMBAGA (CU) DENGAN PEMBERIAN PAKAN PSEUDOMONAS FLUORESCENS PADA MEDIA JERAMI - AJENG DIAH VITALOCHA, GALUH A.D. (Universitas Negeri Surabaya, 2012)
Paramaecium caudatum to high copper metal in the water, because it can be used as an indicator of environtmental pollution. This study aims to determine the level of resistance to copper metal Paramecium caudatum with Pseudomonas fluorescens feeding hay on the media. So it can be used as a landing bioindicator determination of pollution. This study is a study with a control experiment, four treatmants and six repetitions. The study design used was Randomized Complete. Design concentration of copper used in this study was 1 ppm, 2 ppm, and 3 ppm. Data collection is done by calculating the population of Paramaecium caudatum every day for 10 days after breeding in a solution of copper metal. Data analysis using quantitative descriptive statistics where the data is establised in kurva growth. The result showed Paramaecium caudatum resistance to metalic copper in this study were at a concentration of 2 ppm.